A remarkable new species of Eucyphonia (Hemiptera: Membracidae) from Boyacá, Colombia - Rodríguez-Serrano, Juanita; Forero, Dimitri (Zootaxa, 2019)
Eucyphonia festiva sp. nov., is described and illustrated from Santa María, Boyacá on the eastern slope of the Eastern Cordillera of Colombia. Eucyphonia species were previously recorded only from Ecuador, Brazil and Venezuela; thus the new species represents a new generic record for Colombia. This new species was found associated with Piper sp. (Piperaceae), although further confirmation is needed to show that this is a host plant.